Unmasking the effects of E-leadership on virtual team effectiveness by an integrated fsQCA and NCA method - Yining He; Cong Cheng; Limin Wang (PLoS ONE, 2025)
Together with unstoppable trend of business going digitally global in recent years and the worldwide spread-out of COVID-19 since 2020, virtual teams have gradually garnered considerable attention in academia. Yet, the question of how to boost virtual team effectiveness remains underexplored. This study adopts a leadership perspective to examine the role of E-leadership in enhancing virtual team effectiveness. Gathered survey data from 74 virtual teams of Chinese manufacturing firms and employed an integrated fsQCA and NCA method, this study unravels two primary results. First, Fuzzy-set Qualitative Comparative Analysis (fsQCA) identified the sufficient combinations of E-leadership dimensions to promote virtual team effectiveness. Second, Necessary Condition Analysis (NCA) specifies the quantitative thresholds a E-leadership dimension’s value must be to render different levels of virtual team effectiveness. The conclusions of this research offer valuable insights into the theoretical and managerial implications of E-leadership in virtual teams.